Saxa Judaica loquuntur : lessons from early Jewish inscriptions : radboud prestige lectures 2014 - Horst, Pieter Willem van der. (Biblical Interpretation Series, 2015)
In Saxa judaica loquuntur ('Jewish stones speak out'), Pieter W. van der Horst informs the reader about the recent boom in the study of ancient Jewish epigraphy and he demonstrates what kinds of new information this development yields. After sketching the status quaestionis , this book exemplifies the relevance of early Jewish inscriptions by means of a study of Judaism in Asia Minor on the basis of epigraphic material. It also highlights several areas of research for which this material provides us with insights that the Jewish literary sources do not grant us. Furthermore, the book contains a selection of some 50 inscriptions, in both their original languages and English translation with explanatory notes.